Population size and structure of beisa oryx and gerenuk in Geralle National Park, southeastern Ethiopia - Melkamu Aychew; Zerihun Girma (Ecology and Evolution)
Abstract The study was conducted to determine the population size of endangered Oryx beisa (Rüppell, 1835), and near‐threatened Litocranius walleri (Brooke, 1878) of uncertain global population estimates in Geralle National Park, southeastern Ethiopia. Systematic line transects were established with a transect length range of 2.3 to 6.8 km long (a total of 165.4 km long with a sighting distance of 150 m after truncation). The combination of AIC and chi‐square p‐values was used as model selection criteria for density/population size estimation in distance sampling software. The lowest AIC, ∆AIC (close to zero), and Chi‐square tests (p‐value > .05) were selected with adequate model fit. The minimum observation was 67 individuals of beisa oryx in the dry season. The maximum observation was 349 individuals of gerenuk during the wet season. The minimum detection probability of oryx was in the wet season (pâ = 76 ± 26), and the minimum detection probability of gerenuk was (pâ = 75 ± 1) in both seasons. The two‐season pooled density analyzed for studied species indicated (0.85 ± 0.34, 1.24 ± 0.47, beisa oryx/km2), and (3.82 ± 0.6, 4.88 ± 0.7 gerenuk/km2) in dry and wet seasons, respectively. It can be concluded from the results of the study that GNP is home to previously undiscovered healthy populations of the endangered beisa oryx and near‐threatened gerenuk. So it is recommended to undergo in‐depth population studies, including other species available in the national park and their habitat components, so as to design sound, sustainable conservation measures for the wildlife resources in the area.